Relationship between Screen Time and Cardiorespiratory Endurance in Mulawarman University Medical Students Hubungan Screen Time dengan Ketahanan Kardiorespirasi pada Mahasiswa Kedokteran Universitas Mulawarman: The Relationship Between Screen Time and Cardiorespiratory Endurance in Medical Students at Mulawarman University - Rachman, Syarifah Awwaliyyah; Sawitri, Endang; Nugroho, Hary (Jurnal Medika : Karya Ilmiah Kesehatan, 2024)
Cardiorespiratory fitness (CRF) is the ability of the circulatory and respiratory systems to supply oxygen during sustained physical activity. One of the factors that affect cardiorespiratory fitness is sedentary behavior and lifestyle. One indicator of sedentary behavior is screen time (ST). The purpose of this study was to determine the relationship between ST and CRF. This cross-sectional study obtained primary data from 92 students of the Medical Study Program, Faculty of Medicine, Mulawarman University who were selected using a purposive sampling technique. Screen Time Questionnaire (STQ) instrument was used for collecting ST data and Queens College 3-Minute Step Test for CRF. Data analysis was done using Spearman’s correlation test. The results showed that the majority of respondents were 20 years old (39.1%), female (57.6%), with normal body mass index (60.9%). The average daily screen time is 6.00-22.17 hours per day with a median value of 10.60 hours per day. The most frequent CRF group was moderate (46.7%). The relationship between ST and CRF showed p value of 0.250 (p>0.05). Therefore, it is concluded that there was no relationship found between ST and CRF in Mulawarman University Medical Students.